2020
DOI: 10.3390/ijerph17228641
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy for Cardiac Rehabilitation: An Examination of Associated Illness Perceptions, Self-Efficacy, Motivation and Physical Activity

Abstract: Following a diagnosis of cardiovascular disease there is a need for patients to self-manage. Health literacy has been shown to be lower in patients with cardiovascular disease, yet research into health literacy in this population is limited. This study used the Health Literacy Questionnaire (HLQ) to examine the health literacy and associated health, health behaviours and psychological profiles of cardiac rehabilitation patients from a remote and rural regional programme in the Scottish Highlands. Consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(65 reference statements)
3
4
1
Order By: Relevance
“…These results suggest that the population is passive in the health environment and that it may not be self-sufficient in seeking and critically analyzing information or in making any related decisions. These results are consistent with those of the above Spanish study that used the HLQ [ 25 ] and with those of another study performed in the United Kingdom [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that the population is passive in the health environment and that it may not be self-sufficient in seeking and critically analyzing information or in making any related decisions. These results are consistent with those of the above Spanish study that used the HLQ [ 25 ] and with those of another study performed in the United Kingdom [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the current literature, educational level and health literacy appeared positively related [ 5 , 10 , 25 , 26 , 30 , 34 , 35 , 36 ]. In all these studies, those who had completed secondary education returned significantly higher scores for dimensions 5 “appraisal of health information”, 8 “ability to find good health information”, and 9 “understands health information well enough to know what to do” compared to those who had not finished it.…”
Section: Discussionsupporting
confidence: 92%
“…9 Similarly, a Scottish study that examined 5 distinct health literacy profiles in a cardiac rehabilitation setting reported that people with a range of lower health literacy profiles tended to be physically inactive. 10 Moreover, although the degree of association between health literacy and BMI and smoking differ in previous studies, our study found that patients with lower health literacy were more likely to have a higher BMI and to be smokers. These results are in line with the AHA scientific statement, which states that health literacy is associated with a healthier lifestyle and favorable behaviors.…”
Section: Discussioncontrasting
confidence: 72%
“…This concurred with previous studies on patients with COPD and cardiovascular disease, which showed that those with insu cient health literacy also experienced more emotional representations. 58,59 The current study also showed higher self-e cacy and higher QoL among patients with su cient health literacy compared to those with insu cient health literacy, which is in line with previous research. 60,61 These ndings suggest that improving patients' health literacy may improve their self-e cacy, which in turn may positively in uence their QoL.…”
Section: Discussionsupporting
confidence: 92%